Factors Associated with the Incidence of Thyroid Carcinoma at Mohammad Hoesin Hospital, Palembang - Umar, Mulawan; Ad duri, Ahmad Shahaf; Pariyana, Pariyana; Qodir, Nur; Rasyid, Riana Sari Puspita (Indonesian Journal of Cancer, 2025)
Background: Thyroid carcinoma is the most common endocrine malignancy, with its incidence continuously increasing annually. In Indonesia, thyroid cancer represents one of the highest prevalence malignancies, with cases projected to rise each year. This study aims to determine the risk factors associated with the incidence of thyroid carcinoma at Mohammad Hoesin Hospital, Palembang.Method: This study is a case-control observational analytic study using secondary medical record data of thyroid carcinoma patients as a case group and non-carcinoma patients as a control group in the Surgery Department of Mohammad Hoesin Hospital, Palembang, from January 2022 to December 2023, selected by simple random sampling. This study will process and analyze data using univariate analysis methods, bivariate analysis with the Chi-square test, and multivariate analysis with binary logistic regression using SPSS statistical software 29 version.Results: The study included 65 thyroid carcinoma patients as the case group and 65 non-carcinoma patients as the control group. Factors influencing thyroid carcinoma were gender (p 0.001), age (p 0.001), BMI (p 0.001), and history of thyroid disease (p 0.001). Conclusion: This study demonstrated a strong and statistically significant influence of gender, age, BMI, and a history of prior thyroid disease on the likelihood of developing thyroid cancer. These findings underscore the critical importance of these demographic and clinical factors in the risk assessment and screening of individuals for thyroid carcinoma in this population.